Evidence for three factors of perfectionism: Perfectionistic Strivings, Order, and Perfectionistic Concerns. (October 2015) - Kim, Lisa E.; Chen, Lanhowe; MacCann, Carolyn; Karlov, Lisa; Kleitman, Sabina
Abstract: The factor structure of perfectionism is inconsistent across models. Most models distinguish between adaptive and maladaptive aspects of perfectionism, but often do not include elements representing order. Order, however, is theoretically important and distinct from the broad adaptive perfectionism factor. Therefore, a three-factor model of perfectionism was tested in a sample of undergraduate students ( N  = 208) who completed the Almost Perfect Scale-Revised and the Frost Multidimensional Perfectionism Scale. According to the chi-squared difference test and CFI differences, model fit improved when representing Order as a separate factor. In addition, Order and Perfectionistic Strivings factors showed significantly different correlations with Conscientiousness and Neuroticism, academic performance expectation, and four achievement goal orientations, providing further evidence of their distinctiveness. Therefore, including Order as a separate factor represents a better model of perfectionism.